Managing psychophysical readiness in student athletes at law institutes of higher education - Vera S. Makeeva; Sergei N. Barkalov; Valentina N. Pushkina; Nikolai V. Olyashev (Rossijskij psihologičeskij žurnal.)
Introduction. Student athletes should be involved in assessment and self-assessment of psychophysical conditions. These psychophysical conditions reflect their physiological status, functional stability, and physical readiness that contribute to taking care of health, physical improvement, adhering to regulations of the institute of higher education, and changing the lifestyle in accordance with the objectives. The lack of scientific knowledge on self-assessment of psychophysical conditions is a problem for effective managing student athletes’ sports training. Such a work helps to maintain student athletes’ psychophysical readiness for competitive activities during their studies at a law institute of higher education. The novelty of the study lies in student athletes’ training in managing their psychophysical conditions after their self-assessment. Materials and Methods. Student athletes had to master the information on the criteria of health. The study employed the assessing program which included a number of control exercises, functional trials, tests, tasks, and computational methods. These were the methods for assessing the functional state of the cardiovascular system, respiratory system, physical development, and anthropometric data. Taken together these parameters reflected their psychophysical condition. The efficiency of managing the process of education and training depended on the following: (a) control activities; (b) knowledge differentiation and specialization; (c) optimal solutions; (d) associations between substantive and procedural aspects of measured indicators. This promotes student athletes’ motivation for conscious control and strategic self-regulation of psychophysical conditions. Results. During the experiment student athletes have changed the common knowledge of their body functioning. Study participants studied how to manage their psychophysical conditions on the basis of profound knowledge, individual experience of measuring and interpreting the results of control exercises, functional trials, and computational methods. Methods of self-control contribute to revealing the cause and effect relationship, prediction, revealing weak link, choosing of solutions, drafting individual training programs, predicting diseases and injuries, and the coach – athlete interaction at a high-level subject relationship. Discussion. Thus, the practical mastering the methods of self-assessment of conditions contributed to effective managing the process of education and training, and also competitive activities.